Benzohexacene guide in accurate determination of field effect carrier mobilities in long acenes. Issue 2 (23rd December 2021) - Bedel Pereira, E.; Bassaler, J.; Laval, H.; Holec, J.; Monflier, R.; Mesnilgrente, F.; Salvagnac, L.; Daran, E.; Duployer, B.; Tenailleau, C.; Gourdon, A.; Jancarik, A.; et al.
Abstract : Four-probes mobility vs. V GS in the linear regime ( V DS = −10 V) for benzohexacene based transistor. Abstract : Oligoacenes are promising materials in the field of electronic devices since they exhibit high charge carrier mobility and more particularly as a semiconductor in thin film transistors. Herein, we investigate the field effect charge carrier mobility of benzohexacene, recently obtained by cheletropic decarbonylation at moderate temperature. Initially, high performance bottom contact organic thin-film transistors (OTFTs) were fabricated using tetracene to validate the fabrication process. For easier comparison, the geometries and channel sizes of the fabricated devices are the same for the two acenes. The charge transport in OTFTs being closely related to the organic thin film at the dielectric/organic semiconductor interface, the structural and morphological features of the thin films of both materials are therefore studied according to deposition conditions. Finally, by extracting relevant device parameters the benzohexacene based OTFT shows a four-probe contact-corrected hole mobility value of up to 0.2 cm 2 V −1 s −1 .